2022
DOI: 10.3389/fonc.2022.933925
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Four-Gene Ferroptosis Signature for Predicting Overall Survival of Lung Squamous Cell Carcinoma

Abstract: BackgroundLung squamous cell carcinoma (LUSC) represents 30% of all non-small cell lung carcinoma. Targeted therapy is not sufficient for LUSC patients because of the low frequency of targeted-effective mutation in LUSC whereas immunotherapy offers more options for patients with LUSC. We explored a ferroptosis-related prognostic signature that can potentially assess the prognosis and immunotherapy efficacy of LUSC patients.MethodsA total of 502 LUSC patients were downloaded from The Cancer Genome Atlas (TCGA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The TIDE algorithm had been widely used in other studies for predicting immune responses. Wang et al identified a ferroptosis-related model and applied the TIDE algorithm to show that low-risk patients could benefit more from immunotherapies for lung squamous cell carcinoma 42 . Zhou et al established a pyroptosis-based LncRNA model and also calculated the TIDE algorithm to forecast immune responses of their signature in kidney cancer 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The TIDE algorithm had been widely used in other studies for predicting immune responses. Wang et al identified a ferroptosis-related model and applied the TIDE algorithm to show that low-risk patients could benefit more from immunotherapies for lung squamous cell carcinoma 42 . Zhou et al established a pyroptosis-based LncRNA model and also calculated the TIDE algorithm to forecast immune responses of their signature in kidney cancer 43 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified the IL18R1 expression level using the RNA data of 49 normal lung and 502 LUSC tissues derived from the Cancer Genome Atlas (TCGA) website and 288 normal lung tissues derived from Genotype-Tissue Expression (GTEx) website ( 11 , 12 ). The data included the two (TPM and FPKM) types.…”
Section: Methodsmentioning
confidence: 99%